Two Intellectual Landmarks in the Year 1749. Issue 2 (June 2019) - Rassekh, Farhad
Abstract : In the year 1749 Adam Smith conceived his theory of commercial liberty and David Hume laid the foundation of his monetary theory. These two intellectual developments, despite their brevity, heralded a paradigm shift in economic thinking. Smith expanded and promulgated his theory over the course of his scholarly career, culminating in the publication of The Wealth of Nations in 1776. Hume elaborated on the constituents of his monetary framework in several essays that were published in 1752. Although Smith and Hume devised their economic theories in 1749 independently, these theories complemented each other and to a considerable extent created the structure of classical economics.